SKETSA PEMBELAJARAN BAHASA BERBASIS HIGH ORDER THINKING SKILLS (HOTS) DALAM SENTUHAN LITERASI - Florianus Dus Arifian (PGSD UNIKA SANTU PAULUS RUTENG, 2021)
This article is motivated by the issue of not embracing the HOTS dimension in the praxis of learning and the teacher's misperception about the HOTS concept. Therefore, this article aims to explined the HOTS dimension in the praxis of learning and to explained the meaning of HOTS concepts. However, the HOTS theme discussed in this article is focused on the language field. This article was compiled using reading and recording techniques by critically the views of various literary materials. The results of the study show that HOTS-based language learning contained in harmony with modern literacy competencies in the form of the ability to connect text and context and reflect critically on the relationship between text and context.